(untitled) (Research, Society and Development, 2025)
Introduction: Goodpasture syndrome is a rare and severe autoimmune condition characterized by the presence of anti-glomerular basement membrane (anti-GBM) antibodies, leading to rapidly progressive glomerulonephritis and diffuse alveolar hemorrhage. Despite its low prevalence, its fulminant course and the need for early diagnosis make its study crucial. Objective: This study aims to characterize Goodpasture syndrome, from pathogenesis to treatment, presenting robust scientific evidence about the disease. Materials and Methods: An integrative literature review was carried out in indexed databases such as PubMed MEDLINE, SCIELO, Ebscohost, Google Scholar and the Virtual Health Library (BVS) using the descriptors "Goodpasture Syndrome", "Anti-glomerular basement membrane disease" and "Pathophysiology". Articles published between 2014 and 2024 were selected, prioritizing clinical studies, systematic reviews and international guidelines. Data were critically analyzed, focusing on diagnosis, treatment and prognosis. Results and Discussion: The review identified that early diagnosis relies on the detection of anti-GBM antibodies in serum or renal tissue, associated with clinical and radiological findings of pulmonary and renal involvement. Treatment involves plasmapheresis, corticosteroids, and immunosuppressants, with new evidence suggesting the potential of biological therapies, such as rituximab, for refractory cases. Renal survival is directly related to the timeliness of intervention. Conclusion: Goodpasture syndrome remains a diagnostic and therapeutic challenge. Early identification and aggressive treatment are crucial for prognosis, highlighting the importance of continuous updates on new therapeutic strategies.